Editorial: Educators as Architects of Engagement and Community - Thomas D. Dyer (Journal of Scholarly Engagement)
Since our last issue, we have welcomed two new esteemed members to our editorial board, Dr. Jamie Els and Dr. Aimee Whiteside. Their extensive experience and dedication to the field of scholarly engagement have already proven invaluable as they join us in shaping the direction of the journal. Their fresh perspectives and insights will undoubtedly enrich our discussions and broaden our horizons in the pursuit of scholarly excellence. We are excited as they join an already elite team of scholars, Dr. Laura Cruz, Dr. Jean Mandernach, and Dr. Dalia Sherif.